2017
DOI: 10.1038/srep44256
|View full text |Cite
|
Sign up to set email alerts
|

The acute airway inflammation induced by PM2.5 exposure and the treatment of essential oils in Balb/c mice

Abstract: PM2.5 is the main particulate air pollutant whose aerodynamic diameter is less than 2.5 micron. The inflammation of various respiratory diseases are associated with PM2.5 inhalation. Pro-inflammatory cytokine IL-1β generated from effected cells usually plays a crucial role in many kinds of lung inflammatory reactions. The exacerbation of Th immune responses are identified in some PM2.5 related diseases. To elucidate the underlying mechanism of PM2.5-induced acute lung inflammation, we exposed Balb/c mice to PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 52 publications
1
63
1
1
Order By: Relevance
“…However, our previous study showed that there was no significant difference in the level of IL-1β mRNA between PM 2.5 -and saline-induced mice. 23 This may be related to the complex regulation mechanism from gene to protein, such as noncoding RNAs, or the peak levels of gene transcription and protein translation may be not at the same time point, 41 which we will explore further. Meanwhile, we also observed that level of IL-18 protein was increased in the cardiac tissues of PM 2.5 -induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous study showed that there was no significant difference in the level of IL-1β mRNA between PM 2.5 -and saline-induced mice. 23 This may be related to the complex regulation mechanism from gene to protein, such as noncoding RNAs, or the peak levels of gene transcription and protein translation may be not at the same time point, 41 which we will explore further. Meanwhile, we also observed that level of IL-18 protein was increased in the cardiac tissues of PM 2.5 -induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing PM 2.5 in the air, the incidence of respiratory diseases, including pneumonia, asthma and COPD, will gradually increase. Recently, several types of TCMs have been used to treat PM 2.5 -induced respiratory diseases (27)(28)(29). A recent study reported that tuberostemonine could attenuate acute cigarette smoke-induced inflammation of the lung via inhibiting the infiltration of inflammatory cells through decreasing chemokine expression (30).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo research in mice, that is using specific knockout strains and monoclonal antibodies, can provide additional insights into potential mechanisms how air pollution can modulate (allergic) airway inflammation and offer the opportunity to validate hypotheses that have been generated by human studies. First, during acute DEPs-induced inflammatory lung responses, an increased expression of IL-1b 58,59,64,[169][170][171][172][173][174][175][176][177] and GM-CSF 139,178 in BALF and lung tissue were observed, whereas 1 study reported IL-25, IL-33 and TSLP as undetectable. 139 Moreover, the increased IL-1b and GM-CSF levels could be linked to PM or DEPs-induced inflammation and AHR.…”
Section: Particulate Matter and Type 2-promoting Cytokines: Expressmentioning
confidence: 99%